Aggressive driving : insights derived from psychology's general aggression model - Lin, Yusheng, 1976- (Criminal justice (LFB Scholarly Publishing LLC), 2013)
Lin uses two separate studies with independent samples and different measures to explore how self-control personality traits - sensation seeking, impulsivity, CFC, and anger/temper arousal - relate to risky driving and aggressive driving within the framework of the GAM. He extends low self-control theory by demonstrating how the personality traits involved in this construct are associated with criminal/analogue deviant behaviors. The findings not only validate the meditational model of the GAM, but also imply that it could serve as a useful framework to study violent/property crime in future r.